Synthesis and Characterization of 4,4’-Dimethoxy-1,1’-[(butane-1,4-diyldioxy)bis(nitrilomethylidyne)]dibenzene - Ding, Yu-Jie; Wang, Yang; Gao, Jian-Gang (Asian Journal of Chemistry, 2013)
The compound 4,4'-dimethoxy-1,1'-[(butane-1,4-diyldioxy)bis(nitrilomethylidyne)]dibenzene with the molecular formula C20H24N2O4 was synthesized by the reaction of 4-methoxybenzaldehyde with 1,4-bis(aminooxy)butane in ethanol medium and characterized structurally by X-ray crystallography. Intermolecular C-H...O hydrogen bonding is observed between C-H of methoxy groups and O atom from methoxy groups of the neighboring compound molecules. It is noted that the distances between the nearest benzene rings, which are parallel to that of another molecule, are about 2.466(2) Å in the crystal structure, exhibiting strong intermolecular p-p stacking interactions, which forms two-dimensional structures of the title compound.